Using subtraction of perfect squares, it is found that the factored expression is:
9t² - 4 = (3t - 2)(3t + 2).
<h3>What is the subtraction of perfect squares factoring?</h3>
It is given as follows:
a^2 - b^2 = (a - b)(a + b)
In this problem, the binomial is given as follows:
9t² - 4.
Hence:
Hence the factored expression is:
9t² - 4 = (3t - 2)(3t + 2).
More can be learned about subtraction of perfect squares at brainly.com/question/16948935
#SPJ1
Answer:
I think a or C
Step-by-step explanation:
Answer:
4 better xplanation inbox
Step-by-step explanation:
Answer:
562.5
Step-by-step explanation:
i=?
p=3750
r=3*1/100=3/100
t=5 years
I=P*R*T
3750*5*3/100
=5625/100
=562.5